Cardiac Magnetic Resonance for Evaluating Catheter Related FDG Avidity. (27th October 2016) - Jeong, Daniel; Gage, Kenneth L.; Berman, Claudia G.; Montilla-Soler, Jaime L.
Abstract : A 53-year-old female with a history of metastatic left arm melanoma presented for F(18) fluorodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) which showed a moderately FDG avid focus at her port catheter tip near the cavoatrial junction. Although catheter tip related FDG avidity has previously been suggested to be bland thrombus or infection, melanoma can metastasize to unusual locations including the superior vena cava. In addition, the patient had an elevated risk of anticoagulation due to a history of hemorrhagic brain metastases. Therefore, confirmatory cardiac magnetic resonance (CMR) was obtained and findings were consistent with bland catheter-related thrombus.